Attitudes Toward COVID-19 Vaccines in Chinese Adolescents - Cai, Hong; Bai, Wei; Liu, Shou; Liu, Huanzhong; Chen, Xu; Qi, Han; Liu, Rui; Cheung, Teris; Su, Zhaohui; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Medicine, 2021)
Abstract Background: As COVID-19 vaccination programs are being implemented widely, it is important to examine the attitudes of adolescents toward the COVID-19 vaccine uptake. The aim of this study was to examine the acceptance of and attitudes toward COVID-19 vaccines, and their associated factors among adolescents in China. Methods: This was a cross-sectional, observational study conducted between November 27, 2020 and March 12, 2021 using snowball sampling method. Basic sociodemographic characteristics, health-related information, severity of depressive and anxiety symptoms, attitudes and behavior towards COVID-19 vaccines were assessed. Results: Overall, 1,057 adolescents participated in this study, yielding a response rate of 89.3%. There were 799 (75.59%) (95%CI: 73.00-78.18%) adolescents who would accept future COVID-19 vaccination. Binary logistic regression analysis revealed that adolescents who previously heard about COVID-19 vaccines (P=0.001, OR=1.90, 95%CI:1.32-2.74), who thought that COVID-19 vaccines could protect them from COVID-19 infection (P=0.002, OR=2.93, 95%CI: 1.49-5.70), and those who encouraged their family members and friends to get vaccinated (P<0.001, OR= 12.19, 95%CI: 6.78-21.92) and who believed that vaccines are safe (P=0.012, OR=3.94, 95%CI: 1.36-11.44) were more likely to accept future COVID-19 vaccination. In addition, younger adolescents (P=0.003, OR=0.93, 95%CI: 0.89-0.98) were more likely to accept future COVID-19 vaccines than older adolescents. Conclusions: In conclusion, Chinese adolescents appeared to have positive attitudes towards COVID-19 vaccines. It is important to increase public confidence and knowledge regarding the efficacy and safety of COVID-19 vaccines to maximize the success of vaccination programs.